Co-producing health care - pragmatic principles and an illustration [version 2; peer review: 2 approved] - Axel Kaehne; Edmund Horowicz; Lucy Bray (Emerald Publishing, 2020)
Co-production has received increasing attention from managers and researchers in public services. In the health care sector, co-production has become a by-word for the meaningful engagement of patients yet there is still a lack of knowledge around what works when co-producing services. The paper sets out a set of pragmatic principles which may guide anyone embarking on co-producing health care services, and provides an illustration of a co-produced Young People's Health Research Group in England. We conclude by outlining some learning points which are useful when establishing co-production projects.